STUDYING THE HADITH THROUGH ASBABUL WURUD: AN ANALYSIS OF THE HADITH ABOUT THE CHILD OF ADULTERY - Siska Juliana Putri; Tiara Gita Safitri; Wahyu Saputra; Rahmatsyah Mulia Batubara; Laila Sari Masyhur (International Journal of Multidisciplinary Reseach, 2025)
This research discusses the importance of studying asbabul wurud in understanding the hadith of the Prophet Muhammad SAW contextually. The main focus of this research is on the hadith that states that children resulting from adultery are assigned to their mothers, not to the man who committed adultery. This hadith is often debated, especially in the realm of Islamic family law and the protection of children's rights. Using a qualitative approach and literature study methods, this research analyzes the social, cultural, and historical context behind the birth of this hadith. The results of the study show that determining a mother's lineage is not just a legal provision but also a form of protection for the dignity and rights of children born from relationships outside of legal marriage. Through the understanding of asbabul wurud, this hadith is understood as a form of solution to social problems during the time of the Prophet, as well as containing universal values of justice and benefit. This research confirms that a contextual approach to hadith is very important to prevent errors in the interpretation and application of Islamic law. Thus, asbabul wurud becomes an important instrument in maintaining the relevance of Islamic teachings amidst social changes in modern society.